Hubungan Faktor Cuaca dengan Kejadian Demam Berdarah di Kabupaten Bantul - Wahyu Widyantoro; Nurjazuli Nurjazuli; Yusniar Hanani Darundianti (Universitas Aisyah Pringsewu, 2021)
Dengue hemorrhagic fever (DHF) is still becoming epidemic stage in Indonesia. Climate and weather are variable that determine ecological aspect. The ecological aspect consist of DHF. The aim of this research is to analyze the association betwen climate factors (humidity, temperature, rainfall) and dengue cases in Bantul Regency during 2016–2020. This research is quantitative using an ecology time-series study approach. The data analysis used in this study was univariate and bivariate analysis using the Spearman-rho correlation test by testing the relationship between the variables of temperature, humidity, rainfall, and the incidence of DHF. The temperature variable shows a significant value, and the correlation coefficient value will be stronger if the temperature fluctuations in the previous two months (lag 2) are associated with the incidence of DHF. The value of p (0.0000) less than (0.05) with a value of r = 0.515. The humidity variable, the significance value and the correlation coefficient value will be stronger if the fluctuation of air humidity in the previous month (lag 1) is associated with the incidence of DHF. The value of p (0.001) less than (0.05) with a value of r = 0.417. The rainfall variable, the significance value and the correlation coefficient value only showed that in the previous two months (lag2), it was associated with the incidence of DHF, p-value (0.0023) less than (0.05) with r=0.299. The increase in the incidence of DHF in Bantul Regency will tend to follow the fluctuation or increase in the average rainfall in the previous two months. It is an early warning that can signal that there will be an increase in cases of dengue outbreaks. Demam berdarah dengue (DBD) masih merupakan kasus penyakit endemis di Indonesia. Faktor iklim dan cuaca merupakan variabel penting dalam menentukan ekologi, perkembangan, kelangsungan hidup, dan perilaku nyamuk Aedes sebagai vektor utama DBD. Penelitian ini bertujuan untuk menganalisis hubungan antara faktor iklim (kelembaban, suhu, curah hujan) dan kasus DBD di Kabupaten Bantul selama tahun 2016–2020. Penelitian ini bersifat kuantitatif dengan menggunakan pendekatan studi ecology time series. Analisis data yang digunakan dalam penelitian ini adalah univariat dan analisis bivariate mengunakan uji korelasi Spearman-rho dengan menguji hubungan variabel suhu, kelembaban, curah hujan, dan kejadian DBD. Variabel suhu menunjukan nilai signifikansi dan nilai koefisien korelasi semakin kuat apabila fluktuasi suhu pada dua bulan sebelumnya (lag 2) dihubungkan dengan kejadian DBD. Nilai p (0,0000) kurang dari (0,05) dengan nilai r=0,515. Variabel kelembaban, nilai signifikansi dan nilai koefisien korelasi akan semakin kuat apabila fluktuasi kelembaban udara pada satu bulan sebelumnya (lag 1) dihubungkan dengan kejadian DBD. Nilai p (0,001) kurang dari (0,05) dengan nilai r=0,417. Variabel curah hujan, nilai signifikansi dan nilai koefisien korelasi hanya menunjukan pada 2 bulan sebelumnya (lag2) dihubungkan dengan kejadian DBD niilai p (0,0023) kurang dari (0,05) dengan nilai r=0,299. Peningkatan kejadian DBD di Kabupaten Bantul akan cenderung mengikuti fluktuasi atau peningkatan rata-rata curah hujan pada dua bulan sebelumnya. Perlu adanya kewaspadaan sebelum terjadinya peningkatan kasus KLB penyakit DBD.